Poor prognoses of open globe injuries with concomitant orbital fractures. (3rd July 2020) - Gaier, Eric D.; Tarabishy, Sami; Bayers, Christopher; Wolkow, Natalie; Gardiner, Matthew; Lefebvre, Daniel R.; Grob, Seanna
ABSTRACT: Purpose: Orbital trauma, particularly with open globe injury, can have a wide range of visual outcomes, which can be difficult to predict at presentation. Clinical features on presentation may provide insight into visual prognosis. We hypothesized that patients with open globe injuries and concomitant orbital fractures have poorer visual outcomes than patients without orbital fractures. Methods: We reviewed the charts of 77 patients with isolated open globe injuries (OG) and 76 patients with open globe injuries and concomitant orbital fractures (OGOF). Multivariate regression analysis was performed to assess the relative influence of individual presenting historical and clinical features on visual outcome. Results: OGOF patients were more likely to have sustained blunt trauma than a sharp, penetrating injury compared to OG patients. Ocular wound locations were more posterior and likely to involve multiple zones in OGOF compared to OG patients. Among OGOF patients, orbital floor fractures were the most common and roof fractures were the least common, but the latter was associated with presenting NLP vision and multiple zone involvement. The presence of an orbital fracture independently increased the odds of subsequent evisceration/enucleation (OR: 4.6, 95% CI 1.3–20.1, p = .0246) and NLP vision (OR: 6.81, 95% CI 2.42–21.85, p = .0005) when controlling for zone, mechanism of injury, uveal prolapse and demographic variables. Conclusions: The presence of an orbital fracture independently confers a worse visual and ocular prognosis in patients with open globe injuries. Patients with open globe injuries in this category should be appropriately counseled.